Співвідношення двоїстості та критерії екстремальності елемента для задачі відшукання відстані між двома опуклими множинами лінійного нормованого простору - Гудима, У.В.; Гнатюк, В.О. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2018)
У статті для задачі відшукання відстані між двома опуклими множинами лінійного нормованого простору встановлено співвідношення двоїстості, яке зводить розглядувану задачу до задачі на обчислення верхньої межі в спряженому до лінійного нормованого простору просторі. An important problem, the partial case of which is the problem of the best approximation of an element of a linear normed space by a convex set of this space, is the problem of finding the distance between two convex sets of linear normed space, which is considered in this paper. In the article establishes the relation of duality for this problem, which reduces this problem to the problem of evaluationing the upper bound in the conjugate space. The obtained relation is used to obtain the criterion of the extremality of an element. Thes results are used to find the distance between two bullets and between the bullet and the hyperplane of the linear normed space